Listening is an act of love [videorecording (DVD)] : a StoryCorps special, with additional animated shorts! - Rauch, Mike; Rauch, Tim (PBS, 2013)
The first-ever animated feature from StoryCorps celebrates the transformative power of listening. Presents stories from ten years of the innovative oral history project, where everyday people sit down together to ask life's important questions and share stories from their lives.